(untitled) (Baghdad Science Journal, 2022)
Endothelin-I (ET-I) is one of the potent vasoconstrictors secreted from endothelial cells when needed. Many studies revealed the elevation of serum ET-I with human diabetes and microangiopathies. Since insulin resistance is a case of mixed diabetic and pre-diabetic cases, many risk factors beyond obesity and inflammation are proposed. The current study aims to demonstrate the association between serum ET-I and asymmetric dimethylarginine (ADMA) and insulin resistance in type 2 diabetes mellitus (T2DM). Sera of 73 subjects were enrolled currently (control= 35 subjects, and 38 with T2DM for more than 7 years), aged (40-60) years old, with distinct body mass index (BMI) ≤ 25 for control volunteers and (BMI) ≥ 25 for obesity and diabetes patients. Peripheral serum ET-I and ADMA levels were significantly (P≤ 0.0001) higher in T2DM than the control subjects. Receiver operating characteristic curve analysis regarded ET-I and ADMA as good markers for T2DM disease and insulin resistance, correlations between ET-I and anthropometrics revealed a strong increase of urotensin-II (UII), ADMA, homeostatic model assessment for insulin resistance (HOMA-IR) and hemoglobin A1C (HbA1C) with an increase of ET-I. These results are supported by the data of multiple regression analysis, showing that HOMA-IR, HbA1C, UII, BMI, and mean arterial pressure (MAP) are related to ET-I independently. The endothelin-I and ADMA had a positive relationship with increase insulin resistance and may serve as prognostic and diagnostic clinical biomarkers of insulin resistance. Collectively, Therefore, these measurements could evaluate the incidence of DM, and help to better rise up the knowledge about the progression of DM complications.